1995
DOI: 10.1177/096032719501400803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pyridostigmine pretreatment on cardiorespiratory function in tabun poisoning

Abstract: 1 The effect of pyridostigmine on cardiorespiratory func tion after oxime+atropine injection was investigated in tabun poisoned guinea-pigs and without tabun poisoning. 2 The trachea, a carotid artery and jugular vein were can nulated in female urethane-anaesthetised Pirbright white guinea-pigs. After baseline measurements the ani mals received pyridostigmine (0.05 μmol kg-1) and 30 min later atropine (29.5 μmol kg-1) plus obidoxime, HI 6 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Our results showing an initial hypertensive response with a more delayed hypotension effect are consistent with a number of studies, including studies of rats with DFP intoxication (Yen et al 2001 ), rabbits with paraoxon exposure (Kullmann and Uerdingen 1978 ), and hens with tabun exposure (Worek et al 1995 ). Smith and colleagues showed that administration of a muscarinic receptor agonist decreased BP but a hypertensive response was observed when co-administered with a peripheral muscarinic receptor antagonist, suggesting that activation of central muscarinic receptors increased BP (Smith et al 2001 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showing an initial hypertensive response with a more delayed hypotension effect are consistent with a number of studies, including studies of rats with DFP intoxication (Yen et al 2001 ), rabbits with paraoxon exposure (Kullmann and Uerdingen 1978 ), and hens with tabun exposure (Worek et al 1995 ). Smith and colleagues showed that administration of a muscarinic receptor agonist decreased BP but a hypertensive response was observed when co-administered with a peripheral muscarinic receptor antagonist, suggesting that activation of central muscarinic receptors increased BP (Smith et al 2001 ).…”
Section: Discussionsupporting
confidence: 91%
“…The most dramatic increases in PR with PB pretreatment and postexposure antidotal administration are seen with exposure to soman (GD). PB also significantly enhanced the efficacy of atropine and 2-pralidoxime chloride against tabun (GA) both in mice and in guinea pigs (Koplovitz et al 1992a) and achieved PRs of 4 to 12 in exposed animals (Joiner et al 1988;Koplovitz and Stewart 1994), although a subsequent study (Worek et al 1995b) warned that PB pretreatment in guinea pigs could enhance circulatory depression induced by postexposure treatment with atropine and oximes. The PR of postexposure antidotal treatment with atropine and an oxime in poisoning by GF was found to be 1.4 in the mouse and 2.7 in the guinea pig (Stewart and Koplovitz 1993); the addition of PB pretreatment in these species did not change the PR in the mouse and raised the PR in the guinea pig from 2.7 only minimally (and not significantly), to 3.4 (Stewart and Koplovitz 1993).…”
Section: How Does Pb Work As a Pretreatment For Nerve-agent Intoxicatmentioning
confidence: 99%
“…¤ Signi cant, p • :05 versus baseline, ANOVA with Dunnett's post hoc tests. Worek, Kleine, and Szinicz (1995) also studied the effects of PB (0.05 ¹mol/kg) in urethane-anesthetized guinea pigs. They demonstrated a decrease in mean arterial pressure, but found no change in heart rate or respiratory minute volume.…”
Section: Figurementioning
confidence: 99%